Parental Views on Screen Time Intensity and Effects on Preschoolers’ Social Development - Nasywa Ariella Nityasa Ricardo; Meiske Yunithree Suparman (Komunitas Dosen Indonesia, 2025)
The development of digital technology has led to an increase in the use of electronic devices by preschool children. This phenomenon has raised concerns about the impact of screen time intensity on children's social skills, especially in the context of direct interaction and emotional development. Guided by ecological systems theory and social learning theory, this study examines how parental perceptions of screen time intensity relate to the social skills of preschool children in Bantul Regency, Indonesia. Using a quantitative correlational design, data were obtained from 50 parents through validated Screen Time and Social Skills Improvement System (SSIS) scales. Data were collected using questionnaires on screen time intensity and children's social skills, then analyzed using the Pearson Product Moment correlation test with the help of SPSS version 25.0. The results of the analysis showed a significant negative relationship between screen time intensity and preschool children's social skills (r = -0.612; p < 0.000). Sub-dimension analyses reveal that empathy (M = 1.70; SD = 0.63) is the most affected, followed by communication and cooperation. Gender and age analyses show no significant differences, indicating that screen time effects are consistent across demographic subgroups. These findings underscore the critical role of parental supervision in balancing digital engagement and direct social interaction. Practical implications for early childhood education programs and parental guidance strategies are also discussed.